PENGARUH SKEPTISISME PROFESIONAL, ETIKA, TIPE KEPRIBADIAN, KOMPENSASI, DAN PENGALAMAN PADA PENDETEKSIAN KECURANGAN - Arwinda Sari, Kadek Gita; Wirakusuma, Made Gede; Ratnadi, Ni Made Dwi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.01.TAHUN 2018, 2018)
This research aims to obtain empirical evidence of influence of profesional scepticism, ethics, personality types, compensation, and experience in the detection of fraud. The ability of Auditors in detecting fraud can be affected by the characteristics possessed by the auditor, whether Auditors personal characteristics as well as characteristics of beyond personal auditor. One of the personal characteristics that influence the detection of fraud profesional scepticism is owned by an auditor. Other personal characteristics that can affect detection of fraud is ethics, personality types, and experience. In addition compensation is one of the characteristics of the outside auditors that affects personal detection of fraud. The fifth of these characteristics will certainly affect how the ability of Auditors in detecting fraud. Theoretical studies used in this research is attribution theory. Method of determination of the sample used in this study is a nonprobability sampling method with purposive sampling technique, namely the auditor investigative audit ever and ever commissioned in the work field. The sample in this research is 66 people auditor. Data analysis techniques used in this research is the analysis of Multiple Linear Regression. Research instrument has passed the test validity and reliability. The regression model is also a classic assumption has been tested. The results showed profesional scepticism, ethics, compensation, and experience the positive effect on the detection of fraud, while personality type has no effect on detection of fraud.